RBM7 suppresses mitochondrial dysfunction and ferroptosis by destabilizing FBXL16 mRNA to enhance Temozolomide resistance in glioblastoma - Nan Liu; YeTing Cui; Juan Li; SuMei Li; YanYang Tu; JunLi Huo; TongCun Zhang; HaiNing Zhen (Molecular Genetics and Genomics, 2026)

Corrigendum to “Characterization, bioactivity and pharmacokinetic study of a novel carbohydrate-peptide polymer: Glycol-split heparin-endostatin2 (GSHP-ES2)” [Carbohydrate Polymers 207 (2019) 79–90] - Feng Sun; Zhendong Wang; Zhifang Yang; Yan Li; Huifei Cui; Chunhui Liu; Dezong Gao; Fengshan Wang; Haining Tan (Carbohydrate Polymers, 2026)

Environmental filtering of microbial specialists drives divergent C, N, and S cycling in grasslands: Vegetation buffering maintains microbial diversity amidst soil moisture contrasts - Yiming Dai; Haining Wang; Qixiu Cheng; Yiming Zhang; Ye Cui; Huan Ma; Xiaoyu Li; Daolong Xu; Jin Chen (CATENA, 2026)

Tailoring reactive oxidative species (ROSs) cascades in a tandem non-thermal plasma/defect-engineered TiO2 system for enhanced degradation of flotation reagent-laden brine: Unlocking synergistic ROSs generation and pathways - Siyuan Zhang; Xuri Li; Liang Ma; Chunyan Wang; Zhongmei Song; Haining Liu; Xiangmei Cui; Xiushen Ye (Chemical Engineering Journal, 2026)

Responses of microbial community to different depths in volcanic soils of Nvshan Volcano - Jin Chen; Haining Wang; Ye Cui; Yiming Dai; Yueming Bao; Rui Qin; Qixiu Cheng; Xiaoyu Li (World Journal of Microbiology and Biotechnology, 2025)

Copper doped carbon dots for selective determination of regulated aniline additives and safe hair dyeing - Zhanghong Guo; Lin Zhou; Liping Zhang; Haining Cui; Jinxin Ma; Chan Wang; Qijun Song (Analytica Chimica Acta, 2025)

Shrub alters the spatial patterns of nematode taxonomic and functional diversity on the Qinghai-Tibet Plateau - Anning Zhang; Jingwei Chen; Hanwen Cui; Jiajia Wang; Shuyan Chen; Haining Gao; Xiaoxuan Jiang; Sa Xiao; Lizhe An; Pierre Legendre (Plant and Soil, 2024)

Butylparaben induces glycolipid metabolic disorders in mice via disruption of gut microbiota and FXR signaling - Haining Du; Lili Cui; Xinyi Zhao; Ziteng Yu; Tianyue He; Boya Zhang; Xingpei Fan; Meimei Zhao; Ruijiao Zhu; Ziyi Zhang; Mengcong Li; Jiaxin Li; et al. (Journal of Hazardous Materials, 2024)

Integrating CdIn2S4 semiconductors with S-vacancy MoS2 nanosheets to fabricate a multi-channel aptasensing chip for photoelectrochemical detection of multiple mycotoxins - Jing Qian; Huiyuan Yang; Haining Cui; Kawtar Ettayri; Fuheng You; Kun Wang; Jie Wei; Chengquan Wang (Analytica Chimica Acta, 2024)

The first detection of mpox virus DNA from wastewater in China - Jin Xu; Chao Liu; Qun Zhang; Haining Zhu; Feng Cui; Zhiqiang Zhao; Mingfang Song; Bo Zhou; Yunxiao Zhang; Peilong Hu; Lei Li; Qin Wang; et al. (Science of The Total Environment, 2024)

Grazing induces positive direct effect of shrubs on nematode diversity but suppresses indirect effects through microbial pathways - Hanwen Cui; Ziyang Liu; Jingwei Chen; Jiajia Wang; Hongxian Song; Haining Gao; Shuyan Chen; Yajun Wang; Kun Liu; Sa Xiao; Lizhe An; Uffe N. Nielsen (Plant and Soil, 2024)

Spatially selective defect management of CsPbI3 films for high-performance carbon-based inorganic perovskite solar cells - Hailiang Wang; Qixian Zhang; Zedong Lin; Huicong Liu; Xiaozhen Wei; Yongfa Song; Chunyu Lv; Weiping Li; Liqun Zhu; Kexiang Wang; Zhenhua Cui; Lan Wang; et al. (Science Bulletin, 2024)

Assembly mechanisms of microbial communities in plastisphere related to species taxonomic types and habitat niches - Yi Sun; Hongjun Li; Jinyong Zhang; Haining Wang; Xiaoyu Cui; Xin Gao; Wenwen Qiao; Yuyi Yang (Marine Pollution Bulletin, 2024)

Fabrication of a disposable aptasensing chip for simultaneous label-free detection of four common coexisting mycotoxins - Jing Qian; Yue Liu; Haining Cui; Huiyuan Yang; Mustafa Hussain; Kun Wang; Jie Wei; Lingliang Long; Lijun Ding; Chengquan Wang (Analytica Chimica Acta, 2023)

Warming affects herbaceous germination, early survival, and growth by shifting plant-soil microbe interactions in an alpine ecosystem - Jiajia Wang; Stephen Patrick Bonser; Kun Liu; Ziyang Liu; Haining Gao; Hanwen Cui; Jingwei Chen; Yajun Wang; Hongxian Song; Lihua Meng; Xiaoli Yang; Xiangtai Wang; et al. (Plant and Soil, 2023)

Shrub and precipitation interactions shape functional diversity of nematode communities on the Qinghai–Tibet Plateau - Anning Zhang; Shuyan Chen; Jingwei Chen; Hanwen Cui; Xiaoxuan Jiang; Sa Xiao; Jiajia Wang; Haining Gao; Lizhe An; Pedro Cardoso (Global Change Biology, 2023)
Land use and climate change alter biodiversity patterns and ecosystem functioning worldwide. Land abandonment with consequent shrub encroachment and changes in precipitation gradients are known factors in global change. Yet, the consequences of interactions between these factors on the functional diversity of belowground communities remain insufficiently explored. Here, we investigated the dominant shrub effects on the functional diversity of soil nematode communities along a precipitation gradient on the Qinghai–Tibet Plateau. We collected three functional traits (life‐history C – P value, body mass, and diet) and calculated the functional alpha and beta diversity of nematode communities using kernel density n ‐dimensional hypervolumes. We found that shrubs did not significantly alter the functional richness and dispersion, but significantly decreased the functional beta diversity of nematode communities in a pattern of functional homogenization. Shrubs benefited nematodes with longer life‐history, larger body mass, and higher trophic levels. Moreover, the shrub effects on the functional diversity of nematodes depended strongly on precipitation. Increasing precipitation reversed the effects shrubs have on the functional richness and dispersion from negative to positive but amplified the negative effects shrubs have on functional beta diversity of nematodes. Benefactor shrubs had stronger effects on the functional alpha and beta diversity of nematodes than allelopathic shrubs along a precipitation gradient. A piecewise structural equation model showed that shrubs and its interactions with precipitation indirectly increased the functional richness and dispersion through plant biomass and soil total nitrogen, whereas it directly decreased the functional beta diversity. Our study reveals the expected changes in soil nematode functional diversity following shrub encroachment and precipitation, advancing our understanding of global climate change on nematode communities on the Qinghai–Tibet Plateau.

Suppressing “Coffee ring effect” to deposit high-quality CsPbI3 perovskite films by drop casting - Qixian Zhang; Huicong Liu; Xue Tan; Hailiang Wang; Yongfa Song; Xiaozhen Wei; Yue Deng; Weiping Li; Liqun Zhu; Zhenhua Cui; Yang Bai; Haining Chen (Chemical Engineering Journal, 2023)

Waveform Design Using Coprime Frequency-Modulated Pulse Trains for Reverberation Suppression of Active Sonar - Xiaobin Cui; Cheng Chi; Shuqiu Li; Zigao Li; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2022)
Over the last two decades, low-frequency active sonar has become an attractive tool for underwater target detection. The reverberation to signal ratio (RSR) of transmitted waveforms is an important factor affecting the detection capability of low-frequency active sonar. Therefore, reasonable waveform design for reverberation suppression of active sonar is an important topic. Pulse trains of linear frequency-modulated (PTFM) waveforms have been proposed and manifested their good performance in suppressing reverberation. The number of sub-pulses is positively related to the reverberation to signal ratio; the lower the number of sub-pulses, the lower the reverberation to signal ratio. However, to avoid ambiguity in a Doppler measurement, the PTFM waveforms have a requirement for the number of sub-pulses to be satisfied, which prevents its reverberation suppression performance from being further improved. In this paper, we propose a coprime pulse train of linear frequency-modulated (CPTFM) waveform, which reduces the number of sub-pulses to some extent. Therefore, the ability of reverberation suppression of the CPTFM waveform can be improved. The RSR was chosen as the metric to evaluate the waveform’s ability to suppress reverberation, and the theoretical formula for the RSR of the CPTFM waveform was derived in zone A and B. With the overlap of zones A and B brought about by the decrease in the number of sub-pulses, the average RSR of zones A and B is used in this paper to evaluate the reverberation suppression ability of the waveform. The simulation experiment shows that the proposed CPTFM waveform decreases the average RSR by 7 dB and 20 dB in comparison to the reference PTFM waveform and continuous waveform (CW), which is consistent with the theoretical results by the derived formulas.

Parametric Knocking Performance Investigation of Spark Ignition Natural Gas Engines and Dual Fuel Engines - La Xiang; Gerasimos Theotokatos; Haining Cui; Keda Xu; Hongkai Ben; Yu Ding (Journal of Marine Science and Engineering, 2020)
Both spark ignition (SI) natural gas engines and compression ignition (CI) dual fuel (DF) engines suffer from knocking when the unburnt mixture ignites spontaneously prior to the flame front arrival. In this study, a parametric investigation is performed on the knocking performance of these two engine types by using the GT-Power software. An SI natural gas engine and a DF engine are modelled by employing a two-zone zero-dimensional combustion model, which uses Wiebe function to determine the combustion rate and provides adequate prediction of the unburnt zone temperature, which is crucial for the knocking prediction. The developed models are validated against experimentally measured parameters and are subsequently used for performing parametric investigations. The derived results are analysed to quantify the effect of the compression ratio, air-fuel equivalence ratio and ignition timing on both engines as well as the effect of pilot fuel energy proportion on the DF engine. The results demonstrate that the compression ratio of the investigated SI and DF engines must be limited to 11 and 16.5, respectively, for avoiding knocking occurrence. The ignition timing for the SI and the DF engines must be controlled after −38°CA and 3°CA, respectively. A higher pilot fuel energy proportion between 5% and 15% results in increasing the knocking tendency and intensity for the DF Engine at high loads. This study results in better insights on the impacts of the investigated engine design and operating settings for natural gas (NG)-fuelled engines, thus it can provide useful support for obtaining the optimal settings targeting a desired combustion behaviour and engine performance while attenuating the knocking tendency.

Transesterification of Rapeseed Oil to Biodiesel on CaO/α-Fe Hollow Fiber Catalyst: Optimization by Response Surface Methodology - Lin Lin; Xiaoqiang Li; Fengjie Cui; Haining Zhou; Xiangqian Shen; Mingdong Dong (BioEnergy Research, 2012)